Improving problem solving with subgoal labels in expository text and worked examples. (April 2016) - Margulieux, Lauren E.; Catrambone, Richard
Abstract: In highly procedural problem solving, procedures are typically taught with context-independent expository text that conceptually describes a procedure and context-dependent worked examples that concretely demonstrate a procedure. Subgoal labels have been used in worked examples to improve problem solving performance. The effect of subgoal labels in expository text, however, has not been explored. The present study examined the efficacy of subgoal labeled expository text and worked examples for programming education. The results show that learners who received subgoal labels in both the text and example are able to solve novel problems better than those who did not. In addition, subgoal labels in the text appear to have a different, rather than an additive, effect on learners compared to subgoal labels in the example. Specifically, subgoal labels in the text appear to help the learner articulate the procedure, and subgoal labels in the example appear to help the learner apply the procedure. Highlights: Subgoal labels have previously been used to improve learning from worked examples. We tested using subgoal labels to improve learning from abstract textual instructions. Subgoal labeled instructions and examples together improved problem solving. The effect of subgoal labeled instructions does not seem to be additive.